Integrated management of yellows of ginger - DOHROO, N.P. (Indian Phytopathology, 2002)
Yellows (Fusarium oxysporum f. sp. zingiberi Trujillo) is one of the serious diseases of ginger in Himachal Pradesh. In India, the disease was first reported from Madhya Pradesh by Haware and Joshi and subsequently from Himachal Pradesh as a pre-emergence rot causing 40 per cent losses. F. oxysporum is a major and pre-dominant wilt pathogen resulting in yellows of ginger. Yellows of ginger is seed transmitted, and the fungus also survives in the form of chlamydospores in the field year after year. The management of the disease has been reported by the use of seed treatment with maneozeb and carbendazim but no work has been reported on the integrated management of yellows of ginger in field. Keeping this in view, a field experiment was conducted fortwo consecutive years (1991 and 1992) to test the efficacy of seed treatment with maneozeb + carbendazim and biocontrol agents to manage the disease.